2015
DOI: 10.1175/jamc-d-14-0183.1
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite View of the Radiative Impact of Clouds on Surface Downward Fluxes in the Tibetan Plateau

Abstract: Using 13 yr of satellite observations for the Tibetan Plateau, the sensitivities (or partial derivatives) of daytime surface downward shortwave and longwave fluxes with respect to changes in cloud cover and cloud optical thickness are investigated and quantified. Coincident cloud and surface flux retrievals from the NASA Moderate Resolution Imaging Spectroradiometer and the Clouds and the Earth's Radiant Energy System, respectively, as well as ground-based observations at 11 stations across the plateau are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Based on the statistic results of Figure 1, we found that clouds are more distributed during the warm season than the cold season, and this finding may be due to a plentiful supply of moisture during the warm season [101]. In addition, based on long-term cloud records from NASA Clouds and CERES, Naud et al [102] recorded a higher cloud fraction in the northern part of the TP in the winter and a lower cloud fraction in the summer, findings which are consistent with our results. Our results also indicated that cold rain caused by ice clouds dominated precipitation frequency over the TP during the cold season [14] (see Figure 9); Choi et al [19] highlighted that an increase in the dust frequency during the cold season (e.g., winter and spring seasons) over mid-latitude regions of the Northern Hemisphere is derived from a decrease in the supercooled water cloud fraction that effectively glaciates supercooled water clouds by lifted dust aerosols.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on the statistic results of Figure 1, we found that clouds are more distributed during the warm season than the cold season, and this finding may be due to a plentiful supply of moisture during the warm season [101]. In addition, based on long-term cloud records from NASA Clouds and CERES, Naud et al [102] recorded a higher cloud fraction in the northern part of the TP in the winter and a lower cloud fraction in the summer, findings which are consistent with our results. Our results also indicated that cold rain caused by ice clouds dominated precipitation frequency over the TP during the cold season [14] (see Figure 9); Choi et al [19] highlighted that an increase in the dust frequency during the cold season (e.g., winter and spring seasons) over mid-latitude regions of the Northern Hemisphere is derived from a decrease in the supercooled water cloud fraction that effectively glaciates supercooled water clouds by lifted dust aerosols.…”
Section: Discussionmentioning
confidence: 80%
“…For the TP regions, the super-cooled water cloud is more than the warm water cloud, especially in the southeastern part of the TP. In addition, The spatial and seasonal variability in the cloud fraction over the TP (Figure 4) may be induced by water vapor and aerosol loading conditions [50,102]. Besides, more ice clouds during the cold season may be linked with atmospheric temperature and microphysical properties (e.g., ice nuclei aerosol) [21,102].…”
Section: Discussionmentioning
confidence: 99%
“…A critical open question is how water vapor will increase in the future, and in particular, how it will increase with elevation. Furthermore, both cloud cover and cloud optical thickness can influence d(ΔTmin)/dz through their effect on surface downward longwave radiation (DLR) (e.g., Naud et al 2014). However, Naud et al (2013) showed that the DLR-q relationship is not appreciably affected by the absence or presence of clouds.…”
Section: Resultsmentioning
confidence: 99%
“…e 1.0°× 1.0°gridded surface DLR and ULR are provided in SYN1deg Ed3A data. CERES surface fluxes are calculated using a radiative transfer model provided by the Global Modeling and Assimilation Office and MODIS-derived cloud and aerosol properties [23,29]; these calculations are then constrained and fixed by observed TOA outgoing fluxes [30].…”
Section: Datamentioning
confidence: 99%